Disseminated nocardiosis due to Nocardia terpenica. Issue 9 (September 2021) - Matsuo, Takahiro; Nakaoka, Hiroshi; Mori, Nobuyoshi; Sakurai, Aki; Jinta, Torahiko; Nishimura, Naoki; Tamura, Tomohide; Gonoi, Tohru; Furukawa, Keiichi; Chohnabayashi, Naohiko
Abstract: We report the first case of disseminated nocardiosis due to trimethoprim/sulfamethoxazole-resistant Nocardia terpenica successfully treated with meropenem and clarithromycin. The patient travelled to Japan from Australia via Southeast Asia, which led to differential diagnoses of multiple lung nodules including miliary tuberculosis and melioidosis as well as nocardiosis. Because of variety of susceptibility depending on the Nocardia species, clinicians need to confirm the species and investigate its susceptibility.